The control of Chagas' disease transmission in Mambaí, Goiás-Brazil (1980-1981) - Philip Davis Marsden; Domingos das Virgens; Cleudson Nery Castro; Ibiraci Pacífico Brasil; Raul Ferreira; Antonio Carlos Silveira; Carlos Alberto da Silveira Matos; Vanize Macedo; Aluizio Prata (Revista da Sociedade Brasileira de Medicina Tropical, 1983)
BHC application in Mambai in 1980 resulted in a significant decline but not elimination of domiciliated T. infestans. T. sordida peridomestic populations persist and could pose a threat to interupting human transmission of T. cruzi The results of one massive attack spray application alone was compared with this application plus one selective application as regards the presence of T. infestans in houses oneyear later. No significance difference could be detected. It is likely that for interruption of T. infestans transmission cheaper procedures can be devised than those currently in use. A further pilot study of a virgin community afflicted by T. infestans transmission is indicated since Mambai cannot be regarded as a representative areafor those still awaiting insecticide application.